Hubungan Self-Control dan Self-Confidence dengan Impulsive Buying pada Anggota Female Daily Network - Mey Nurlika; Kartika Nuradina; Rifqi Farisan Akbar (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
The rapid growth of digital beauty communities has increased consumers’ exposure to product information, reviews, promotions, and trends that may encourage spontaneous purchasing. This study examines the relationships between self-control, self-confidence, and impulsive buying among Female Daily Network members. A quantitative correlational design with a cross-sectional approach was employed. The study involved 100 respondents selected through purposive sampling, and data were collected using an online questionnaire with a five-point Likert scale. The data were analyzed using Spearman’s rank correlation. The results showed that self-control had a positive, strong, and significant relationship with impulsive buying (rs = 0.763; p < 0.001). Self-confidence also had a positive and significant relationship with impulsive buying, although the strength of the relationship was relatively weak (rS = 0.292; p = 0.003). The positive relationship between self-control and impulsive buying differs from the general theoretical expectation and may reflect a gap between perceived self-control and actual purchasing behavior in digital beauty consumption. Consumers may perceive themselves as capable of regulating their decisions while still making spontaneous purchases when products are associated with appearance, identity, preferences, or current beauty trends. These findings indicate that impulsive buying is related not only to internal psychological characteristics but also to situational and digital stimuli surrounding consumers. Future research should examine other psychological variables and employ consumption-specific measures to provide a more comprehensive explanation of impulsive buying.